Didactics of African Languages and English for Specific Purposes: Integrated Approaches for Hybrid Learning - Ibrahima KARAMOKO & Nongoiala Sidiky SILUE (Akofena)
This article proposes a reflection on the integration of African languages and English for specialization in a hybrid teaching approach. The objective is twofold: to examine the linguistic and didactic interconnection between these two domains, and to formulate practical recommendations to improve their co-learning in multilingual contexts. Two questions inform the study: how can the coexistence of African languages and English enrich hybrid learning? What didactic strategies allow a fruitful interaction between these two linguistic systems? Drawing on the theory of linguistic ecology, the article shows that the teaching of African languages and English for specialization can be enhanced by an interactive learning environment, both face-to-face and digital. A survey both quantitative and qualitative, including a questionnaire, interviews and classroom observations, made it possible to collect data on the effectiveness of hybrid teaching practices. The results reveal that students who actively exploit interactions between their local languages and specialized English show increased skills and a better appropriation of disciplinary concepts. Furthermore, it is suggested that teachers play a crucial role as mediators, using technological tools to facilitate these linguistic and didactic exchanges. The article concludes that the adoption of active methods, such as hybrid interactional analysis, not only does it encourage an optimal use of digital tools, but it also enhances the potential of African languages in a globalized context of specialized learning.